Delivering social work education on inquiry reports addressing harm to vulnerable people: An exploratory study. (January 2018) - Houston, Stan; McColgan, Mary
Summary: This article outlines a research study examining how social work education, in relation to case reviews and inquiry reports, was structured and delivered to a range of social work students in Northern Ireland. Adopting a qualitative design, nine social work educators in the region were interviewed and asked about their approach to presenting findings from the reports to social work students and the issues this raised for the research sample. The results revealed three key themes: the salience of the organizational context; how learning was structured and organized; and the various attempts to build social work competence. Findings: These themes showed that the co-ordinators were delivering a complex area of knowledge. It was clear that they had given considerable thought to the essential messages from the reports even though the constraints of time and setting were apparent. Moreover, they employed a range of innovations in the way the reports were theorized and how the knowledge coming from them was disseminated. The importance of the 'fear factor' within students was a primary issue affecting teaching and learning strategies. Applications: The findings can be used as a foundation for further research into this area, looking at student feedback, the attainment of learning outcomes and, importantly, ways of enhancing teaching and learning approaches on this sensitive area. The research can also contribute to the identification of social work educators' learning needs and how to approach emotionally laden case studies of significant harm to vulnerable individuals.